Design and experimental study of a replaceable steel-UHPC composite bridge deck. (June 2022) - Xiao, Rucheng; Song, Chaolin; Sun, Bin; Guo, Rui; Chen, Hui
Abstract: This paper proposes a prefabricated orthotropic steel-UHPC composite bridge deck consisting of standard units, which could be assembled conveniently in-situ to avoid the traditional complicated steaming curing of UHPC with high temperature. The standard unit can also be replaced separately under conditions of failures or local damage. This composite bridge deck can thus convincingly mitigate the fatigue problem in the orthotropic steel deck and also the pavement damage in traditional steel bridges. A parametric study of the composite bridge deck is performed together with the PBL shear connector to determine a reasonable design of the deck structure. The effects of some key structural parameters, such as the UHPC layer thickness, the steel deck plate thickness, the spacing and stiffness of the open rib, and the size of the PBL shear connectors, are carefully studied by the finite element model analysis. Based on the determined deck design, a full-scale experiment study is further executed to investigate and demonstrate the performance of the proposed structure. Results show that the failure mode of the structure is the yielding of stiffening ribs, while the UHPC panel under a tensile state works well. Moreover, as a new cement-based composite material, UHPC exhibits the improved tensile strength and a strong ability to limit the width of cracks after the test load is removed.